Sistem Informasi Pengarsipan Dokumen Di Kantor Kecamatan Kebakkramat - Wijayanti, Vernanda Anggi; Naury, Chairullah; Naafian, Nuur Rochman (Indonesian Journal of Information Technology and Computing (IMAGING), 2023)
Document archiving is an important activity in every organization or institution, including in the Kebakkramat Subdistrict Office. The documents generated and received by the office need to be stored properly and easily accessible for operational purposes and service to the public. However, there are often several challenges in the manual document archiving process, such as disorganized archiving, slow document retrieval processes, the risk of losing or damaging documents, and limited storage space.The research method used in this study is the SDLC (System Development Life Cycle) waterfall model. The stages of SDLC used include needs analysis, system design, implementation, testing, and maintenance. The information system developed uses PHP programming language and MySQL database. The result of this research is an information system that can be used by the administrative department to digitally manage archives and can be utilized according to needs quickly.Keywords: Information Systems, archiving, document, sdlc, php